Contribution of Sheikh Yusuf Abdullahi Al-Lokoji to the Development of Tijjaniyyah Sufi Order in Lokoja, North Central Nigeria - Abdulrahman Yahaya (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2023)
The paper aimed at discussing the contributions of Sheikh Yusuf Abdullahi Al-Lokoji to the development of Tijjaniyyah Sufi Order in Lokoja, North Central Nigeria. It traces the origin of Lokoja and the factor that led to the settlement of Lokoja town in 1860 during the colonialist as the first administration capital in Northern Nigeria. It sheds light on the introduction of Islam into Lokoja. The paper made use of primary and secondary sources. It discusses the development of Tijjaniyyah Sufi Order and its spread as well as chains of authority that existed earlier in Lokoja before the emergence of Sheikh Ibrahim Niass Kaolack. Finally, the paper provided biography of Sheikh Yusuf Abdullahi Al-Lokoji, his teachings as Sufi scholar in Lokoja and some of his literary works on Tijjaniyyah Sufi Order for the benefit of Muslims.